Tecnologia de construção de Livros de Compromisso das irmandades religiosas em Minas Gerais no século XIX - Bethania Reis Veloso (2017)
This PhD research, developed in the field of the Heritage Science from the field of research of the Technical Art History, aims to analyze two European printed manuals dating from the XVII and XVIII centuries, and two manuscript books produced in Minas Gerais in Mid-nineteenth century, through comparative studies of its formal, stylistic, aesthetic and constructive structures. The printed books selected are manuals widely published in Portuguese America and Spanish America, whose hypothesis of this research determines its influence for the teaching and model for creation of books of commitment of religious brotherhoods in Minas Gerais. This is the printed book entitled Nova Escola para aprender a ler, escrever e contar, of Portuguese origin, dated 1722, and written by the calligrapher Manuel Andrade de Figueiredo (1670-1735). This book dialogues with another printed work entitled Primera parte del arte de escribir todas formas de letras, of Spanish origin, dating from 1650, and written by Joseph de Casanova (1613-1692). From these European models, we selected two manuscript books developed from the guidelines and references of these works: Livro de Compromisso da Irmandade de Nossa Senhora Mãe dos Homens e de São Francisco das Chagas, produced in the city of Catas Altas in 1806, and belonging to the College Caraça; and the Livro de Compromisso da Irmandade de São Benedito from Paracatu city, produced in 1808. These both compromises books are rare examples of high technical and aesthetic quality, coming from distinct regions of Minas Gerais and conforming important documents of the history of Religious culture. The unpublished character of the study of these works is amplified by an innovative methodology, considering the transdisciplinary field of Heritage Science, from the intersection between the areas of Conservation Science, Technical Art History, History of Art, and History of Culture, allowing a broad view of the objects of study, through the intersection among the historical, aesthetical, and material analyzes of the books researched.